Improved biodegradation of pharmaceuticals after mild photocatalytic pretreatment. (13th September 2020) - de Wilt, Arnoud; Arlos, Maricor J.; Servos, Mark R.; Rijnaarts, Huub H. M.; Langenhoff, Alette A. M.; Parker, Wayne J.
Abstract: The combination of photocatalysis and biodegradation was investigated for the removal of nine selected pharmaceuticals as a means to reduce loadings into the environment. The combined process, consisting of a resource‐efficient mild photocatalysis and a subsequent biological treatment, was compared to single processes of intensive photocatalysis and biological treatment. The UV‐TiO2 based photocatalysis effectively removed atorvastatin, atenolol and fluoxetine (>80%). Biological treatment after mild photocatalytic pretreatment removed diclofenac effectively (>99%), while it persisted during the single biological treatment (<50%). Moreover, the biodegradation of atorvastatin, caffeine, gemfibrozil and ibuprofen was enhanced after mild photocatalytic pretreatment compared to biological treatment alone. The enhanced biodegradation of these pharmaceuticals appeared to be triggered by the biodegradation of photocatalytic products. Mild photocatalysis followed by biological treatment is an effective and resource‐efficient combination for pharmaceutical removal that could substantially reduce the loading of pharmaceuticals into the environment.